AhR activation increases IL-2 production by alloresponding CD4(+) T cells initiating the differentiation of mucosal-homing Tim3(+)Lag3(+) Tr1 cells - Ehrlich, Allison K. (Eur J Immunol, 2017)
Activation of the aryl hydrocarbon receptor (AhR) by immunosuppressive ligands promotes the development of regulatory T (Treg) cells. Although AhR-induced Foxp3(+) Treg cells have been well studied, much less is known about the development and fate of AhR-induced Type 1 Treg (AhR-Tr1) cells. In the current study, we identified the unique transcriptional and functional changes in murine CD4(+) T cells that accompany the differentiation of AhR-Tr1 cells during the CD4(+) T-cell-dependent phase of an allospecific cytotoxic T lymphocyte (allo-CTL) response. AhR activation increased the expression of genes involved in T-cell activation, immune regulation and chemotaxis, as well as a global downregulation of genes involved in cell cycling. Increased IL-2 production was responsible for the early AhR-Tr1 activation phenotype previously characterized as CD25(+)CTLA4(+)GITR(+) on day 2. The AhR-Tr1 phenotype was further defined by the coexpression of the immunoregulatory receptors Lag3 and Tim3 and non-overlapping expression of CCR4 and CCR9. Consistent with the increased expression of CCR9, real-time imaging showed enhanced migration of AhR-Tr1 cells to the lamina propria of the small intestine and colon. The discovery of mucosal imprinting of AhR-Tr1 cells provides an additional mechanism by which therapeutic AhR ligands can control immunopathology.